Systematic review of Neotropical Lauxaniidae genera Triconopsis Hendel (Diptera, Schizophora) - Silva, Vera Cristina [UNESP] (Sociedade Brasileira de Zoologia, 1998)
A review of the Neotropical Lauxaniidae genus Triconopsis Hendel, 1914 is presented with redescription of T. longicornis Hendel, 1914 and the description of T. caioalbertsi sp.n. (type locality Uruguay), including illustrations and a key.
Keywords: Diptera; Lauxaniidae; Triconopsis; Neotropical region; new species